Improvement in high-temperature oxidation resistance of SiC nanocrystalline ceramics by doping AlN. Issue 21 (1st November 2021) - Li, Zhijian; Guo, Ruru; Li, Lu; Zheng, Ruixiao; Ma, Chaoli
Abstract: AlN-doped SiC nanocrystalline ceramics were prepared by ball milling and reactive liquid-phase spark plasma sintering (SPS), using Si, C and AlN powders as raw materials. The oxidation behavior of the ceramics was studied. The AlN-doped SiC ceramics exhibited excellent oxidation resistance at 1773 K for 50 h and the parabolic rate constant was 0.004 mg 2  cm −4  h −1 . Compared with SiC ceramics, AlN-doped SiC ceramics could inhibit the crystallization of silica, prevent the grain growth of cristobalite and ensure the integrity of oxide scale by healing the possible cracks during the oxidation process, resulting in the improved oxidation resistance.